Medicine Shortages: Gaps Between Countries and Global Perspectives - Acosta, Angela; Vanegas, Egdda Patricia; Rovira, Joan; Godman, Brian; Bochenek, Tomasz (Frontiers in Pharmacology, 2019)
Over the last decade, global health policies and different research areas have focused on the relevance of medicine shortages. Published studies suggest there have been difficulties with access to medicines since the beginning of the twentieth century. Some suggested approaches have enabled advances in our understanding and management of the problem. However, in view of global and regional health care concerns, the phenomena needs to be characterized and described more fully in order to provide evidence about the current types of affected medicines, identified causes, and potential strategies to address this. This study aims to compare the situation regarding shortages between countries in three different regions, analyzing adopted definitions, main causes reported for the shortage’s events, global context and national approaches Methodology: An observational study presented as a narrative review of the situation and findings. Results: Based on the reported cases in the literature, a typology of medicines shortage and supply interruption episodes and its causes were proposed; national approaches to notify and manage the medicines shortages cases were described and classified by update frequency; main differences between market and supply chain manage perspective of the situation were identified global and countries perspectives also were described with emphasis on available definitions. Conclusion: Policy makers require solutions that prevent those cases in which the population's health is affected by episodes of medicine shortages and/or interruption in the supply chain. In addition, to generate a glossary related to logistics management and the availability of medicines will be useful to understand and overcome the phenomena; and to recognize that potential solutions are not only related with actions linked to research, development and innovation as some global perspectives are proposing, but much wider.